Quantitative analysis of povidone-iodine thin films by X-ray photoelectron spectroscopy and their physicochemical properties - Sa Anongtip; Sawatdee Somchai; Phadoongsombut Narubodee; Buatong Wilaiporn; Nakpeng Titpawan; Sritharadol Rutthapol; Srichana Teerapol (Acta Pharmaceutica)
In this study, povidone-iodine (PVP-I) has been formulated as a topical spray to produce a thin film for the controlled release of I2. By means of experimental design, 27 formulations containing glycerol, ethanol, PEG 400, copovidone and HFA 134a as a propellant were prepared. The pH values of all formulations were in the range of 6-7. The viscosity was within the range of 11.9-85.9 mPa s. The surface tensions were 20.3 to 24.6 mN m-1 and the contact angles were between 19.3 and 38.7°. The assays for the iodine contents were within acceptable range (80-120 %). X-ray photoelectron spectroscopy analysis revealed the ionized form of iodine was much higher than the unionized form. The MIC and MBC values of the PVP-I sprays against Staphylococcus aureus, S. epidermidis and Pseudomonas aeruginosa were higher than that of commercial PVP-I solution. The cytotoxicity study confirmed that the PVP-I spray had lower toxic effects on keratinocytes and fibroblasts compared to the commercial PVP-I solution. The formulation containing 59 % ethanol, 18 % copovidone and 12 % PEG 400 showed good antibacterial activity.